O ensino com pesquisa como eixo articulador de uma pedagogia universitária na mobilização da totalidade da cognição - Gomes, Ruth Cristina Soares (2012)
This work presents results from research accomplished in the Academic Master’s degree in Science Teaching in the Amazon, which had as a general objective in what point the to investigate teaching with research is constituted as pedagogical process able mobilize the totality of cognition constituting itself into the articulating axis of a university pedagogy. The research was accomplished at the Center for Advanced Studies in Parintins. The theoretical foundation was anchored in Sternberg (2010), Fonseca (2011), Ghedin (2011), Franco and Pepper (2010), Silva (2011), Masseto (2011) among others that discuss the relevance of teaching with research in process construction of knowledge through critical and reflective participation of students. The methodological route was based by in hermeneutic approach as we sought to interpret in the literature and in the speeches of subjects the meaning of a teaching with research. For this purpose, we used the techniques of bibliographical search, documentary and interviews with teachers and students of biology. The results indicate that the didactic of teaching with research can establish itself as an articulating axis of a university pedagogy which mobilizes various cognitive processes, because it privileges the ability that student has to think, analyze, question and stimulates the critical and reflective action of reality allowing it to act intelligently on it.